THE PHENOTYPE AND FUNCTION OF MONOCYTES IN PATIENTS WITH PULMONARY TUBERCULOSIS - L. V. Sakhno (SPb RAACI, 2014)
Abstract. Peripheral blood monocytes were investigated in the patients with pulmonary tuberculosis. It was established that population of CD14+16+ monocytes was twofold increased in the patients with tuberculosis. The higher level of CD14+CD16+ monocytes was associated with decreasing number of monocytes with intracellular TNF–α, and negative correlation between these parameters was revealed. On the contrary, the higher level of CD14+CD16+ monocytes was connected with increased number of IL–10–producing monocytes. IL–10–producing cells were established mainly in the population of CD16+ monocytes and so population of CD14+CD16+ monocytes may represent the cells with suppressive activity. Really, the CD14+CD16+ monocytes were increased in patients with defective antigen specific response. Enhancement of CD14+CD16+ monocytes was observed in patients with active tuberculosis independently of form and dissemination of disease and did not connected with concomitant viral or bacterial infection. (Med. Immunol., 2005, vol.7, № 1, pp 49556)